Investigation on software‐defined networks' reactive routing against BitTorrent. Issue 5 (1st September 2015) - Vicino, D.; Lung, C.‐H.; Wainer, G.; Dalle, O.
Abstract : Technologies in software‐defined networks (SDNs) introduce programmatic ways to reorganise the network logical topology. A possible practical usage of SDNs is reactive routing, where the logical topology is continuously evolving based on traffic statistics and policies. Usually, the SDNs controllers are considered transparent to the higher layers. It is expected that changes in logical topology may not affect applications. The goal is to study the impact of logical topology changes on BitTorrent, a popular peer‐to‐peer protocol in practice. This study focuses on BitTorrent, and the experimental results show that BitTorrent may produce the opposite effect to the one expected. The authors have run 32 BitTorrent clients in an emulated SDN ring topology and changed the virtual topology periodically by removing one link at the time from the ring. The experiments produced lower propagation when logical topology changed periodically than when it was static for BitTorrent traffic. For comparison, the same experiments were recreated using HTTP. For HTTP, slower propagation is obtained when logical topology changed than when it was static. Finally, the results are discussed and it has been concluded that high layer protocols need to be carefully studied, and in some cases adapted, before being deployed in SDNs.